Extraction of baby java orange peel essential oil (Citrus sinensis (L.) Osbeck) using microwave assisted extraction (MAE) method - Sunyoto, Nimas Mayang Sabrina; Savira, Sylvia; Fahurrozi, Muhamad Imam; Sukardi, Sukardi; Dewi, Ika Atsari; Rusdin, Halimah Hamdani; Pratiwi, Dinda Agustin (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2026)
Baby Java oranges are extensively processed into juices, syrups, and candies, generating peel waste that poses environmental concerns if not properly utilized. The peels are rich in essential oils with significant industrial potential. Conventional extraction methods are time consuming and degrade oil quality due to prolonged heat exposure. This study investigates the effects of microwave power and extraction time on the yield and quality of essential oils extracted from Baby Java orange peels using Microwave-Assisted Extraction (MAE). Randomized Group Design was used with 3 power levels (100, 400, and 600 W) and 3 extraction durations (5, 10, and 15 min). Parameters analyzed included oil yield, specific gravity, refractive index, and color values (L, a*, b*), using two-way ANOVA and DMRT. Results showed that both microwave power and extraction time significantly affected oil yield (1.40-4.57%), specific gravity (1.0353-1.0416 g/mL), and color (L: 13.95-21.02; a*: 2.46-22.00; b*: 0.46-13.31), while refractive index (1.466-1.475) remained unaffected. Interaction effects were significant for specific gravity and color but not for yield or refractive index. These findings demonstrate that MAE provides an efficient and rapid extraction method, enhancing essential oil yield and maintaining quality within reduced processing times.